Psychological Variables In Communication: A Systematic Literature Review On Communication Apprehension Or Anxiety, Willingness To Communicate, And Self-Perceived Communication - Kurdeniansyah, Kurdeniansyah (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Communication functions as a mediating activity that influences individuals’ psychological states, including their psychological well-being, which in turn affects performance and quality of life across various domains. Research on communication anxiety, willingness to communicate, and self-perception in communication forms a core part of communication psychology, a field that examines communicative behaviors in relation to psychological constructs such as self-efficacy, self-esteem, common mental health disorders, grit, growth language mindset, and burnout. This study employs a systematic literature review approach, synthesizing empirical findings from research conducted within the past five to seven years. The review encompasses studies focusing on diverse professional groups, including psychiatrists, students, and educators (such as professors). The results demonstrate a significant association between communication psychology variables and individual performance in professional and academic contexts, with notable implications for psychological well-being. These findings highlight the importance of communication-related psychological factors as a central topic for further research aimed at enhancing individual performance and well-being.